Determinant Factors of Quality of Life at School in Early Adolescents: A Multivariate Analysis - Lestari, Nur Eni; Herliana, Irma (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
School is a primary environment for early adolescents, shaping and influencing various aspects of their quality of life. Therefore, understanding the determinant factors affecting the quality of life at school for early adolescents is essential to creating a supportive and empowering educational environment. The aim of this study was to identify the determinant factors of quality of life at school for early adolescents. This study employs a cross-sectional design. The population of this study includes early adolescents in the Jakarta, Bogor, Depok, Tangerang, and Bekasi areas. The sampling technique used is consecutive sampling, with a total of 558 respondents. This study uses multivariate analysis through multiple logistic regression. The results indicate that gender is not a significant predictor of quality of life at school for early adolescents (Exp(B) = 0.59, CI = 0.24-1.41); school status is also not significant (Exp(B) = 0.91, CI = 0.13-6.37); physical activity has a significantly negative impact on quality of life at school (Exp(B) = 0.21, CI = 0.07-0.64); number of absences from school is not significant (Exp(B) = 1.69, CI = 0.28-10.32); peer relationships have a significantly positive impact (Exp(B) = 7.98, CI = 1.34-47.50); academic stress is not significant (Exp(B) = 1.33, CI = 0.10-17.43); bullying incidents have a very high significantly positive impact (Exp(B) = 67.04, CI = 34.07-131.93); time spent on social media has a significantly positive impact (Exp(B) = 9.05, CI = 4.57-17.90); family support has a significantly strong negative impact (Exp(B) = 0.03, CI = 0.00-0.25); physical school environment is not significant (Exp(B) = 0.35, CI = 0.06-1.98). The factor most related to quality of life at school for early adolescents is bullying incidents. This can serve as a basis for appropriate interventions focused on significant factors to help create a more supportive and empowering educational environment for adolescents.